Penggunaan Platform Matific untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini dalam Mengenal Geometri - Ayu Hopiani; Devi Fitriani; Muh Asriadi AM (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2025)
Childhood is a golden period to stimulate cognitive abilities, including the introduction of geometry that can help children understand shape, space and spatial. This ability is a strong foundation for learning math at the next level. This study aims to improve children's cognitive abilities in recognizing geometry through the use of matific platform. This research is a classroom action research conducted in one of the TX in the district/ city of Sumedang, with a total of 10 children. The research process was carried out in three cycles. The results showed an increase in children's cognitive abilities after doing play activities with the matific platform. The average percentage results in action I amounted to 25.2% with less criteria, action II amounted to 52.4% with good criteria, and action III amounted to 78.8% with very good criteria. The results of the increase are also reinforced by using the N-gain formula which produces a value of 0.716 which is included in the high category. Based on the results of the calculation, it can be concluded that playing activities using matific platform can improve cognitive abilities of early childhood in recognizing geometry.